The The Effect of Green Destination Image on Tourist Revisit Intention through Green Perceived Value and Satisfaction - Ananda Windi Sukosyah; Ananda Sabil Hussein; Ikhtiara Kaideni Isharina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Tourism that embraces environmentally friendly practices plays a vital role in ensuring nature conservation for future generations. This study aims to examine the influence of green destination image on revisit intention, with green perceived value and tourist satisfaction as mediating variables. Using a quantitative approach and purposive sampling, the research involved 200 tourists who had visited Tiga Warna Beach more than once in the past six months. The findings reveal that an environmentally friendly destination image and tourist satisfaction significantly influence tourists' intention to revisit. Furthermore, both green perceived value and tourist satisfaction act as partial mediators, strengthening the relationship between destination image and revisit intention. These results highlight the importance of building a strong green image and enhancing visitor satisfaction to foster loyalty. Tourism managers at Tiga Warna Beach are encouraged to develop strategies that increase return visits, such as promoting conservation efforts and engaging tourists through personalized communication. This study contributes valuable insights into the green tourism sector and may serve as a reference for future research within the service industry, particularly in developing sustainable tourism models that prioritize environmental preservation.